Pengaruh Hambatan Komunikasi Antarbudaya Suku Sunda dengan Non-Sunda terhadap Efektivitas Komunikasi - AnandaLingga Detia; Sarwoprasodjo, Sarwititi (Jurnal Komunikasi Pembangunan, 2017)
Cultural diversity in Indonesia has positive and negative impacts. Generally, the positive impact is becoming a nation’s wealth that could be a capital to unite the nation. In the other hand, the negative impact which occurred if this cultural diversity can not be integrated and well-organized so it will make misinterpret which is ultimately can lead to conflict and discord nation. This study aims to 1) analyze the communication effectiveness, 2) analyze intercultural communication barriers which occurred between Sundanese and non-Sundanese, 3) analyze the influence of intercultural communication barriers on the communication effectiveness between Sundanese and non-Sundanese. The research is located in Tanjungbaru village, Cikarang Timur district, Bekasi Regency considering the number of migrants with diverse ethnics. The methodology of this research was survey research method (explanatory), with the questionnaire as a research instrument, and supported by qualitative data that obtained through in-depth interviews to the informants. The sampling technique that used was simple random sampling with 40 pairs of friends that have different cultures. The statistical analysis used multiple linear regression test that the result showed that there is a significant influence in intercultural communication barriers on communication effectiveness. The most significant influence on the effectiveness communication of the sequential is psychocultural barriers, cultural barriers and environmental barriers.